2008
DOI: 10.2203/dose-response.08-016.scott
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Stimulated Epigenetic Reprogramming of Adaptive-Response Genes in the Lung: An Evolutionary Gift for Mounting Adaptive Protection against Lung Cancer

Abstract: ᮀ Humans are continuously exposed to low-level ionizing radiation from natural sources. However, harsher radiation environments persisted during our planet's early years and mammals survived via an evolutionary gift -a system of radiation-induced natural protective measures (adaptive protection). This system includes antioxidants, DNA repair, apoptosis of severely damaged cells, epigenetically regulated apoptosis (epiapoptosis) pathways that selectively remove precancerous and other aberrant cells, and immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 76 publications
(227 reference statements)
2
67
0
Order By: Relevance
“…Components of the presumed epiregulated system of natural protection can be activated by gamma-ray doses as low as 0.5 mGy above natural background as was demonstrated by Ogura et al (2009) for suppression of spontaneous mutations and the activation likely involves rapid epireprogramming of the genome (Scott et al 2009). This allows for rapidly mounting DNA damage repair, antioxidant production, protective cytokine (e.g., low-level TGF-β1) releases, etc.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Components of the presumed epiregulated system of natural protection can be activated by gamma-ray doses as low as 0.5 mGy above natural background as was demonstrated by Ogura et al (2009) for suppression of spontaneous mutations and the activation likely involves rapid epireprogramming of the genome (Scott et al 2009). This allows for rapidly mounting DNA damage repair, antioxidant production, protective cytokine (e.g., low-level TGF-β1) releases, etc.…”
Section: Discussionmentioning
confidence: 98%
“…These findings support the view that exposure to low radiation doses (mild stresses) increase protective antioxidants which may contribute to hormetic phenotypes. Stochastic low-dose-radiation thresholds are likely involved as well as intercellular signaling, which may be epigenetically regulated (i.e., epiregulated; Scott et al 2009). …”
Section: Benefits Of Low and Moderate Radiation Dosesmentioning
confidence: 99%
See 2 more Smart Citations
“…Large-scale changes in gene expression were repeatedly found in a number of hormetic interventions including irradiation, both heat and cold shocks, repeated mild heat stress, dietary restriction, hypergravity (for review see Vaiserman, 2008), and antioxidant supplementation (Brack et al, 1997). Scott et al (2009) suggested that the hormetic effect may be attributed to induction of the adaptiveresponse genes due to a long-lasting epigenetic memory: once threatening damage of the nuclear DNA occurs, it is quickly recognized with subsequent, rapid up-regulation of the adaptive-response genes.…”
Section: Hormesis: a Kind Of Adaptive Epigenetic Response?mentioning
confidence: 99%